Research on the Reform Path of Dance Teaching Models in Normal Universities under the Background of Innovative Entrepreneurship Education - Li, Quan (Journal of Educational Research and Policies, 2024)
In the global context of innovative entrepreneurship education, for normal universities, as the cradle of training teachers, transforming dance teaching models is particularly important. Traditional dance teaching models often focus on imparting skills while neglecting the cultivation of innovative thinking and practical abilities. By analyzing the connotation of innovative entrepreneurship education and exploring its application in dance teaching, this paper proposes reform paths centered on interdisciplinary collaboration, practice orientation, and optimization of the evaluation system, which can provide both theoretical and practical guidance for the optimization of dance teaching in normal universities.